Influence of a social control model in the public management process of the Provincial Municipality of Pacasmayo, 2020 (SCIÉNDO INGENIUM, 2022)
This article refers to a theme of sociological content (social control) in a public entity such as a provincial municipality of the La Libertad Region, Peru. The objective is to determine the influence of the social control model in the public management process of the Provincial Municipality of Pacasmayo year 2020. Descriptive, non-experimental, pre and post test research with a single group. The population and sample composed of 35 citizens between officials and members of Grassroots Organizations, to whom a Questionnaire prepared by the author was applied on the level of knowledge, practices and attitudes before and after the use of the model of social control proposed for public management. Reliability through Cronbach's Alpha coefficient with pre and post test values ​​of 0.94, 0.98, 0.92, 0.94, 0.85 and 0.91. In the statistical analysis, the SPSS 20 Program and the help of T Student were used. As results, the significant influence on knowledge, practices and attitudes was obtained with values ​​of 6.03, 0.94 and 9.14, respectively, with which it is concluded that the social control model influences the public management process. of the Provincial Municipality of Pacasmayo, year 2020.
Keywords: social control; Public Management; knowledge; practices; attitudes – values